STRATIGRAFI BATUAN DAERAH SELAJAMBE DAN SEKITARNYA, KECAMATAN SELAJAMBE, KABUPATEN KUNINGAN PROPINSI JAWA BARAT - -, Abbas; Hamdani, Ahmad Helman; Muhamadsyah, Faizal (Bulletin of Scientific Contribution, 2015)
Geographically, the research area is located at 108° 27' 7.3548" BT - 108° 32' 7.3572" BT and 07° 0' 9.6336" - 07° 5' 9.6324" LS. Administratively belongs to Selajambe District, Kuningan Regency, West Java. Based on the lithostatigraphy aspect, the research area is divided into four units which are (from the oldest) : Sandstone Unit (Tmbp), Monomic Breccia Unit (Tmbx), Volcanic Breccia Unit (Qbv) and Tuff Unit (Qt).Geological history of the region began at Middle Miocene, research area was deep sea environment, submarine fan depositional system due to turbidite mechanism, to formed sandstone unit (Tmbp). With increasing sediment supply without the accommodation space inadequate to sediment were prograding and made closer the source area, following by sedimentation of rough material to form the monomic breccia unit (Tmbx). At Miocene -Pliocene periods there was an increase of tectonic activity that caused the rocks to folded, jointed and faulted. During the Pleistocene, area of research has become the terrestrial environment and in that time volcanism was occured to formed the volcanic breccia unit (Qbv) and are conformably overlain by tuff unit (Qt) at the top.